Dynamic Fuzzy Cognitive Maps-Based Crowd Analysis Using Time Series Obtained From Video Processing - Altundogan, Turan Goktug; Karakose, Mehmet; Yaman, Orhan; Tanberk, Senem; Mert, Fatih; Yilmaz, Asim Egemen (Ieee-Inst Electrical Electronics Engineers Inc, 2025)
Fuzzy cognitive maps treat the components of a problem or system expressed as fuzzy concepts and model the system with the relationships between these concepts. We predicted that FCM' s approach to calculating with these relationships could perform multivariate time-series forecasting with high performance. However, especially in real-world systems and related data sets, numerical values that clearly express the relationships between time series elements are not included, and this is a challenge. Another challenge that FCMs have for these problems is that real-world systems are highly dynamic structures and these relationships have variable properties in different situations. We evaluated these challenges as the main motivation factor and developed a GA-based method to determine system relationships for different states of the system. Then, in order to dynamically handle these relationships determined for different states on FCM, we took advantage of neural architectures that take the initial concept vectors as input and calculate the relationships between these concepts. In order to evaluate the performance of the time-series forecasting approach we developed, we performed time-series forecasting on two different scenarios using an artificially generated data set and a benchmark data set containing real-world data. In this way, we saw that the time series modeling performance of our proposed system is over 95%. FCMs perform the calculations they have made until the system becomes stable. This allows time series analyses to be performed not only depending on time but also depending on the steady state. Therefore, using this capability of the approach we developed to model time series formed from crowd analysis data obtained with video analytics is quite suitable in terms of providing the contribution points we present in this article. In this context, we integrated our FCM-based time series forecasting approach to two different video analytics scenarios by applying two different crowd analysis approaches we developed within the scope of this study. The success of our proposed method is over 95% both for performing for forecasting the time series obtained as a result of crowd analysis. Beside, crowd analysis approaches developed in this study have similar performance to state of the art approaches in the literature.
Keywords: Time series analysis; Forecasting; Brain modeling; Vectors; Training; Supervised learning; Predictive models; Long short term memory; Computational modeling; Data models; Dynamic fuzzy cognitive maps; deep learning; crowd analysis; time series forecasting; video analytics